Juridical Review of International Private Law in Interfaith Marriages Outside Indonesia (Case Study of the Marriage of Dimas Anggara and Nadine Chandrawinata) - Retno Hirowati; Safina Aliyah Dewi; Dwi Mei Laila; Shofia Hanifah (Journal of Legal and Cultural Analytics, 2023)
One of the most important aspects of Indonesian culture is marriage. One topic that is considered very close to the essence of humanity is marriage. There is much debate about what is meant by marriage, especially when it comes to inter-religious unions that occur outside the Unitary State of the Republic of Indonesia. This case study investigates the legal framework of private international law that regulates interreligious unions that occur outside the Unitary State of the Republic of Indonesia. In the case of interfaith marriages that occur abroad, there is disagreement about the legitimacy or legality of marriage in Indonesia for couples who marry in different religious traditions. UU no. 1/1974 regulates marriage and states, in line with the 1945 Constitution, that no religious law or belief system can legitimize marriage. Every marriage performed outside Indonesia is deemed to have occurred between two Indonesian citizens or between an Indonesian citizen and a foreign citizen, in accordance with Pasal 56 Undang-Undang Nomor 1 Tahun 1974. According to Lex Loci Celebrations, a marriage is perfected in accordance with local law when it is performed in accordance with international private law. Interfaith marriages performed abroad are a kind of legal smuggling which is contrary to pasal 2(1) of international civil law and is regulated by it. Regarding legal certainty and how the status of interfaith marriages entered into abroad is treated, this topic will be discussed in a separate section below.